Deletion of a core APC/C component reveals APC/C function in regulating neuronal USP1 levels and morphology - Day, Jennifer L.; Tirard, Marilyn; Brose, Nils (Frontiers in Molecular Neuroscience, 2024)
The Anaphase Promoting Complex (APC/C), an E3 ubiquitin ligase, plays a key role in cell cycle control, but it is also thought to operate in postmitotic neurons. Most studies linking APC/C function to neuron biology employed perturbations of the APC/C activators, cell division cycle protein 20 (Cdc20) and Cdc20 homologue 1 (Cdh1). However, multiple lines of evidence indicate that Cdh1 and Cdc20 can function in APC/C-independent contexts, so that the effects of their perturbation cannot strictly be linked to APC/C function. We therefore deleted the gene encoding Anaphase Promoting Complex 4 (APC4), a core APC/C component, in neurons cultured from conditional knockout (cKO) mice. Our data indicate that several previously published substrates are actually not APC/C substrates, whereas ubiquitin specific peptidase 1 (USP1) protein levels are altered in APC4 knockout (KO) neurons. We propose a model where the APC/C ubiquitylates USP1 early in development, but later ubiquitylates a substrate directly or indirectly stabilizes USP1. We further discovered a novel role of the APC/C in regulating the number of neurites exiting somata, but we were unable to confirm prior data indicating that the APC/C regulates neurite length, neurite complexity, and synaptogenesis. Finally, we show that APC4 SUMOylation does not impact the ability of the APC/C to control the number of primary neurites or USP1 protein levels. Our data indicate that perturbation studies aimed at dissecting APC/C biology must focus on core APC/C components rather than the APC/C activators, Cdh20 and Cdh1.